Fungsi Investasi Dalam Perspektif Islam - Asyari Hasan; Farid Adhitya Nugraha; Muamar Aditya; Melati Aysah Putri; M. Hibatul Azizi; Hartini Hartini (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The purpose of this study is to reassess how Islam perceives investment regulations. In terms of capital quality, amount, and market, it has been proven that Islamic investment models in Indonesia are ranked lower compared to conventional investments. Therefore, it is necessary to reevaluate the regulations governing Islamic investment from a Shariah maqasid perspective. The data for this study was collected from various literature and reference sources, utilizing trend analysis and a document review approach. According to the research findings, investments that promise significant returns with minimal effort are considered commonplace and acceptable due to their widespread use in society. However, from a financial standpoint, such investments have the potential to disrupt both investor financial stability and currency value stability. Although the initial basis of these investments may be legitimate and halal, selling them using derivative market techniques would involve elements of usury, speculation, and ambiguity, which contradict several Shariah principles as they are not in line with the teachings of Islam regarding ethical investment.